Rabindranath Tagore's Śāntiniketan essays religion, spirituality and philosophy - Tagore, Rabindranath 1861-1941 (Routledge, 2020)
This book provides a critical introduction and translation of fifty ntiniketan (Abode of Peace) essays written by Rabindranath Tagore between 1908 and 1914. It provides key insights into Tagore's fundamental meditations on life, nature, religion, philosophy and the world at large. As the first of its kind, this volume is a definitive collection of Tagore's ntiniketan essays translated into English which contains a substantial amount of scholarly material on them. The essays look at Tagore's ideas of universality, his socio-cultural location along with the development of his thought, his reflections on Buddhism, Vaiavism, Bul philosophy, the Bhagavadgt and to a great extent the Upanishads and their contemporary relevance. It also connects Sri Ramakrishna's concepts of vijnna and bhvamukha with Tagore's thought, an original contribution, through the study of these essays. A nuanced exploration into translation theory and praxis, it fills a lacuna in Tagore Studies by bringing to the fore profound religious, spiritual and philosophical knowledge in Tagore's own voice. This volume will be useful for scholars and researchers of Translation Studies, Tagore Studies, Language and Literature, Cultural Studies and readers interested in Tagore's philosophical ideas